Penanganan Tindak Pidana Penggelapan di Kejaksaan Negeri Kota Cirebon Dalam Perspektif Hukum Positif Dan Hukum Islam - Chelsa Fareza; Leliya Leliya (PEPAKEM: JURNAL HUKUM TATA NEGARA DAN POLITIK ISLAM, 2025)
Embezzlement is an offense against property that originates from the abuse of lawful possession and trust. This study analyzes the handling of embezzlement cases by the Cirebon City District Prosecutor’s Office and compares the offense under Indonesian positive law and Islamic criminal law. It employs empirical legal research with statutory, conceptual, comparative, and institutional approaches. Primary data derive from institutional observation and an interview with a prosecutor, while secondary legal materials include the National Criminal Code, the Criminal Procedure Code, the Prosecutor’s Office Law, classical and contemporary Islamic legal literature, and relevant scholarly works. The data are qualitatively analyzed by examining the elements of the offense, prosecutorial stages, evidentiary requirements, asset recovery, victims’ interests, and the classification of embezzlement in Islamic law. The findings show that embezzlement under Article 486 of Law Number 1 of 2023 requires unlawful appropriation of another person’s property that was already lawfully under the offender’s control, distinguishing it from theft. Prosecutorial handling includes coordination with investigators, review of case files, pre-prosecution, receipt of suspects and evidence, indictment, trial, legal remedies, and execution. In Islamic law, embezzlement is not automatically classified as sariqah subject to hudud because possession was initially obtained without theft. Its characteristics are closer to khiyanah, ghulul, and certain forms of ghasb, making ta'zir the appropriate sanctioning framework. Effective handling should combine legal certainty, proportional punishment, restitution or asset recovery, protection of defendants’ rights, and restoration of victims’ losses.